2011
DOI: 10.1177/1080569911413808
|View full text |Cite
|
Sign up to set email alerts
|

Written and Computer-Mediated Accounting Communication Skills

Abstract: Communication skills are a fundamental personal competency for a successful career in accounting. What is not so obvious is the specific written communication skill set employers look for and the extent those skills are computer mediated. Using survey research, this article explores the particular skills employers desire and their satisfaction level with new hires. Results indicate that basic writing mechanics are the skills in highest demand, followed by effective documentation. Except for email proficiency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 20 publications
2
63
0
3
Order By: Relevance
“…Of the 27 sentences, participants only rated four of them below 3.0. Therefore, nearly every error mentioned was seen as at least somewhat bothersome, further confirming results of Christensen and Rees (2002) and Jones (2011) that these are seen as important skills for entry-level accountants.…”
Section: Most Bothersome Errorssupporting
confidence: 89%
See 4 more Smart Citations
“…Of the 27 sentences, participants only rated four of them below 3.0. Therefore, nearly every error mentioned was seen as at least somewhat bothersome, further confirming results of Christensen and Rees (2002) and Jones (2011) that these are seen as important skills for entry-level accountants.…”
Section: Most Bothersome Errorssupporting
confidence: 89%
“…The first sentence contained the error, and the following sentence was a correct version. 6 The four main grammatical errors covered in our survey were chosen based on the results of Christensen and Rees (2002) and Jones (2011) who found that clarity, grammar, punctuation, and spelling/ proper word usage were some of the most important skills needed by entry-level accountants. The sentences used in the survey were adapted from Gilsdorf and Leonard (2001), Gray and Heuser (2003), Hacker and Sommers (2015), May andMay (2012), andWhittenburg, Flatley, andRaabe (1998).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations